Formulasi Sabun Cair Berbahan Baku Virgin Coconut Oil VCO dengan Penambahan Ekstrak Daun Pepaya Carica Papaya L. untuk Peningkatan Aktivitas Anti Bakteri Staphylococcus Epidermidis ATCC 12238 - Raden Rara Anteng Pujowati; Anna Fitriawati; Tatiana Siska Wardani (EduInovasi: Journal of Basic Educational Studies, 2024)
Acne is a chronic inflammatory disease caused by Staphylococcus epidermidis. Papaya leaves (Carica papaya L.) contain antibacterial substances, namely alkaloids carpaine, flavonoids, tocophenols. Of this study was to determine the physical quality of liquid soap, increasing antibacterial activity. Papaya leaves were extracted with 96% ethanol solvent, then evaporated with a water bath. Antibacterial activity test using the disc diffusion method in concentrations of 5%, 15% and 25% and liquid soap will be made F0 0%, F1 5%, F2 10%, and F3 25% against Staphylococcus epidermidis ATCC 12238. Amoxicillin tab as a positive control and distilled water as a negative control. Bacterial activity appears a clear zone around the disc paper. And see the physical quality test according to the requirements. The results of the bacterial test data are made in table form, and analyzed using the SPSS method Formula with the addition of papaya leaf extract can be made and according to the physical quality conditions of liquid soap. The results of the 25% concentration extract test are an inhibition zone of 20.8 mm, the highest liquid soap formula is an inhibition zone of 23.8 mm in inhibiting the growth of Staphylococcus epidermidis ATCC 12238. Liquid soap preparations and papaya leaf extract have antibacterial activity against Staphylococcus epidermidis ATCC 12238 bacteria and according to the physical quality requirements of liquid soap.